English for Academic Puropses: Moving beyond the confines of the neoliberal university. - Axford, Jill (2015)
There is no doubt that language plays a fundamental role in academic performance. It seems rather perverse then that with the current high proportion of international students on UK university courses, and the wider diversity of students resulting from increased university access, language still seems to be delegated a low status in the university, with English for academic purposes (EAP) courses mainly focused on providing training in transferable language and academic skills within a deficit, remedial approach, in order to gain students fast access to higher education courses, rather than perceiving language as a continuing essential constituent embedded in their academic study. Furthermore the effect of this quick fix approach results in the low profile, segregated and marginalised role of the EAP unit and practitioner. This paper explores the current values, identity and sense of direction of the neoliberal university, the affordances and limitations of the current approaches to teaching EAP, and the possibility that there might be a way forward for EAP to raise its status and profile by becoming a discipline in its own right, thus centralising and adding value to the role of language and academic discourse within the academy, and enhancing and deepening the student academic experience.